РОЗРОБКА ПОЛІМЕРНИХ ПОКРИТТІВ З ЕФЕКТОМ САМОЗМАЩУВАННЯ НА ОСНОВІ ПОЛІІМІДІВ З НАНОЧАСТИНКАМИ ОКСИДУ КРЕМНІЮ - Пащенко, Євген; Савченко, Денис; Кухаренко, Світлана; Кайдаш, Оксана; Курганов, Роман (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2023)
The influence of SiO2 nanoparticles on the improvement of thermal stability and increase of mechanical properties of composites has been studied. It has been shown that the addition of nano-SiO2 in composites is effective in limiting adhesion wear and helping to reduce the coefficient of friction. High thermal stability and high mechanical properties make the manufactured composites a potential material for use in self-lubricating bearings, which are subject to the requirements of low coefficient of friction in discrete mode.